ISLAMIC CHARACTER DEVELOPMENT STRATEGY THROUGH 5S CULTURE (SMILE, GREETING, SALAM, POLITE, COURTESY) FOR STUDENTS AT SMP MUHAMMADIYAH 07 MEDAN - Husni Ayustia; Selamat Pohan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Juvenile delinquency caused by emotional instability and confusion results in several violations that are often committed, such as smoking, skipping school and making fun of teachers often occur in junior high school students, so that it becomes a concern in society. This study uses a qualitative method with a descriptive approach. The results of the study: first, the strategy for developing Islamic character is to provide examples and understanding related to the 5S culture, second, student understanding is carried out both in learning and outside learning.